2010
DOI: 10.1007/s00404-010-1786-5
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy complicating systemic lupus erythematosus: a series of 86 cases

Abstract: Planned pregnancy during stable stage, appropriate treatment in pregnancy and close monitoring can improve the security of pregnancy complicating SLE. In situations that the drug treatment is ineffective and the mother and infant are threatened, or the fetus is mature, the pregnancy should be terminated promptly, thereby reducing the complications, and increasing the success rate of pregnancy and perinatal survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 11 publications
1
24
1
Order By: Relevance
“…SLE patients were more often diagnosed with renal disease before pregnancy. Renal disease is a concern because it has been associated with pregnancy complications, such as hypertension, early-onset preeclampsia, renal flare, fetal loss, preterm births, and low BW (5,(25)(26)(27)(28)(29). However, the rates of renal disease diagnosed before pregnancy in the present study (5% in the first pregnancy and 2.7% in subsequent pregnancies) were lower than those in a previous report (11%) (7).…”
Section: Discussioncontrasting
confidence: 83%
“…SLE patients were more often diagnosed with renal disease before pregnancy. Renal disease is a concern because it has been associated with pregnancy complications, such as hypertension, early-onset preeclampsia, renal flare, fetal loss, preterm births, and low BW (5,(25)(26)(27)(28)(29). However, the rates of renal disease diagnosed before pregnancy in the present study (5% in the first pregnancy and 2.7% in subsequent pregnancies) were lower than those in a previous report (11%) (7).…”
Section: Discussioncontrasting
confidence: 83%
“…Observational studies and every day clinical practice showed that planned pregnancies are associated with lower risk of flare during pregnancy, as compared to unintended pregnancies [44,45]. The EULAR recommendations for women's health and the management of family planning/pregnancy in SLE and/or APS women [46] have proposed a useful 'check-list' of factors to be considered for preconception counselling and risk stratification (synthesized and adapted in Table 1).…”
Section: Preconception Counselling and Pregnancy Monitoringmentioning
confidence: 98%
“…The rate of live and healthy newborns in SLE ranges from 66% to 85% [2]. Pregnancy outcome is strictly related to the disease activity at conception [3].…”
Section: Introductionmentioning
confidence: 99%